ANALISIS PENGARUH STRATEGI POSITIONING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ELEKTRONIK MEREK SAMSUNG DI NEW SUWANDI ELECTRONIC PANGKALPINANG - Churothul A'In, Ina; Ahmad Agin, Arka'a; Medinal (Jurnal Progresif Manajemen Bisnis, 2019)
The purpose of this research is to understand the impact of Positioning Strategies variable for customer purchase decision in purchasing Samsung brand electronic products from New Suwandi Electronic Pangkalpinang. The independent variables which is is studied are Product Attributes (X1), the Benefit of Products (X2), Product Users (X3), Competitor (X4), and The Price (X5) (which is a derivative of the variables positioning strategy) with the dependent variable is Purchase Decision on Cumsumers in Pangkalpinang. The data that is used in this research is primary data which is obtained by quisioner. The sample of this study is 100 respondents of New Suwandi Electronic customers in Pangkalpinang, after that the analysis obtained by using quantitative data analysis covers: Validity and Reliability Test, Normality dan Multicolinearity, Multiple Regression Analysis, Determination Coeffisien Analysis (R2) as well as Hypotesis Testing by F test and t test. The result in regression equation as follows: Y=0,115+0,284X1+0,683X2+0,165X3+0,199X4+(-0,279) Hypotesis test use F test shows are the variables of Product Attributes, Product Benefit, Product Users, Competitor, and Price are indeed proper to test the dependent variable of Purchase Decision. Then through the t test shows the five independent variables analyze significantly proved the influenced the dependent variable of Purchase Decisions. Determination Coeffisien Analysis (R-square) of 71% means the impact of the Purchase Decisions variable can be explained by the five variables, the remaining 29% influenced by all the variables not included in this research.